An assessment framework for smart and sustainable housing for older adults using analytic hierarchy process (AHP) - Ptak-Wojciechowska, Agnieszka; Kort, Helianthe; Kasraian, Dena; Gawlak, Agata (Frontiers in Built Environment, 2024)
IntroductionWhile there is a call for smart and sustainable housing in general and for older adults in particular, little attention is paid to identifying the determinants of such housing and their extent of influence on the quality of life (QoL) of older adults. This study addresses the above gap by re-defining the criteria for house quality assessment, taking into account new needs of older inhabitants, while concerning digital assistive technologies.MethodsThis research uses various methods to identify and validate housing-related criteria and metrics, resulting in a transparent multi-criteria evaluation framework that accounts for the spatial needs of older adults. These include recommendations for multi-criteria decision-making method (MCDM/A), expert workshop to develop new metrics and validate sub-criteria, expert survey to prioritize criteria and sub-criteria and interviews with three employees in the construction-services sector in the Netherlands, to gain knowledge on smart and healthy environments.Results and DiscussionThe results show that age-friendliness of housing function is the most significant criterion, while availability of housing modifications for seniors most important sub-criterion. Our findings can benefit architects in designing improved age- friendly spaces, older adults in evaluating their dwellings and researchers from the field of architecture in selecting most relevant method for their study.